UNSUR BUDAYA DAN KARAKTER TOKOH DALAM NOVEL GAJAH MADA SUMPAH DI MANGUNTUR KARYA LANGIT KRESNA HARIADI - . Sujoko (Jurnal Ilmiah Dikdaya, 2017)
The purpose of this research is to describe the cultural element and the characters in the novel “Gajah Mada Sampah di Manguntur” written by Langit Kresna Hariadi. The method of the research is analytic descriptive in which the process of analyzing and describing the main object of the research. Based on the analysis of the research, it can be concluded that the novel “Gajah Mada Sumpah di Manguntur” comprises cultural element, especially Javanese culture in Majapahit Kingdom era. This matters can be seen from the structure of the event on the novel. The element of reliance towards many things such as believe in the power of dream and believe in the power of magic are found in some sequences of the story. Furthemore, the other element of culture also can be seen from this novel, such as information technology as an interesting fact in which the bird in Majapahit era is used as a tool to deliver information. Moreover, another element of culture that is shown in this novel is the domination of element of language. The characters appear in the novel are devided into 5 (five) characters which are identified as strong characters, such as the character of Gajah Mada. While being a care person, he also protects his country and the people who are needed protection. Besides, he also can work on a team in solving tasks. Moreover, the character of Gajah Enggon is also identified as a strong character in the novel. He is a mainstay who has a unique and deft character. Then, there is a Pradhabasu character who also has a uniue character. Beside his good and nice character, his ability in olah kanuragan (spiritual ability) is an interesting thing in this novel. The next character is Prabu Putri Dyah Wiyat who has an honest character which can be seen from her utterances in saying things with honesty in which she said that she ever involved in forbidden relationship. Keywords : Culture, Characters, Novel